Batoka Gorge Hydroelectric Scheme : A Macroeconomic Assessment of Public Investment Options - World Bank (World Bank, Washington, DC, 2019)
Maximizing the benefits from public sector investments requires a clear, predictable, and transparent process informed by robust analyses that can facilitate multicriteria considerations of different options and alternatives. However, the tools available to governments to assess the costs and benefits of different investment strategies are often too general or specific to determine the optimal investment strategy. This paper aims to improve the tools available to facilitate the assessment of the macroeconomic implications of large infrastructure projects and enhance the capacity for management of public investment decisions. The macroeconomic assessment of public investment options (MAPIO) model was applied to the Batoka Gorge hydroelectric scheme to provide an analysis of impacts on key macroeconomic variables. The MAPIO model shows the project provides a robust financial and economic investment option with a net positive impact on the national economies in both Zambia and Zimbabwe. The estimates are considered conservative and the returns remain robust when subjecting the model to extreme assumptions to test the sensitivity of the results. However, it is important to acknowledge the model limitations, which does not include noneconomic benefits, costs, or impacts on other sectors. Any investment decision should involve a multicriteria assessment that considers the full range of options and alternatives that may be available to achieving the development objectives.